Uruguay : Strengthening Participatory Monitoring and Evaluation of Social Policy - World Bank (Washington, DC, 2013)
The Uruguay Non-lending Technical Assistance (UY NLTA) for Uruguay was undertaken at the request of the Government of Uruguay's Ministry of Social Development (MIDES). Following a devastating financial and macroeconomic crisis in 2002, MIDES was established with a view to coordinating social programs and providing a safety net program for Uruguayans affected by the crisis: the National Assistance Plan of Social Emergency (PANES), which was established in 2005. The objectives of the UY NLTA are to: (i) evaluate the impact of PANES social emergency programs; (ii) inform a dialogue about the future role of social emergency programs and of MIDES as the lead authority responsible for the coordination and oversight of social policy in Uruguay, and (iii) strengthen MIDES capacity to assess, monitor and evaluate social policy in Uruguay, with considerable weight on participatory approaches to monitoring and evaluation.